Neutrophil Mechanosignaling Promotes Integrin Engagement With Endothelial Cells and Motility Within Inflamed Vessels - Morikis, Vasilios A.; Simon, Scott I. (Frontiers in Immunology, 2018)
Neutrophils are the most motile of mammalian cells, a feature that enables them to protect the host against the rapid spread of pathogens from tissue into the circulatory system. A critical process is the recruitment of neutrophils to inflamed endothelium within post-capillary venules. This occurs through cooperation between at least four families of adhesion molecules and G-protein coupled signaling receptors. These adhesion molecules convert the drag force induced sby blood flow acting on the cell surface into bond tension that resists detachment. A common feature of selectin-glycoprotein tethering and integrin-ICAM bond formation is the mechanics by which force acting on these specific receptor-ligand pairs influences their longevity, strength, and topographic organization on the plasma membrane. Another distinctly mechanical aspect of neutrophil guidance is the capacity of adhesive bonds to convert external mechanical force into internal biochemical signals through the transmission of force from the outside-in at focal sites of adhesive traction on inflamed endothelium. Within this region of the plasma membrane, we denote the inflammatory synapse, Ca2+ release and intracellular signaling provide directional cues that guide actin assembly and myosin driven motive force. This review provides an overview of how bond formation and outside-in signaling controls neutrophil recruitment and migration relative to the hydrodynamic shear force of blood flow.